2011
DOI: 10.1073/pnas.1101141108
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual and neural consequences of rapid motion adaptation

Abstract: Nervous systems adapt to the prevailing sensory environment, and the consequences of this adaptation can be observed in the responses of single neurons and in perception. Given the variety of timescales underlying events in the natural world, determining the temporal characteristics of adaptation is important to understanding how perception adjusts to its sensory environment. Previous work has shown that neural adaptation can occur on a timescale of milliseconds, but perceptual adaptation has generally been st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
81
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 60 publications
9
81
0
Order By: Relevance
“…On the other hand, following longer exposure to directional motion the sensor signals a direction opposite to the adapting pattern (i.e., rMAE). Thus, the final output of the second-order model shows effects which mirror those reported by previous psychophysical studies on fast forms of motion adaptation (Kanai and Verstraten 2005;Pavan et al 2009Pavan et al , 2010Glasser et al 2011;Pavan and Skujevskis 2013). The extended Motion Energy Model does not account for another effect previously reported by Kanai and Verstraten (2005) and Pavan et al (2009Pavan et al ( , 2010, called "Perceptual Sensitization" (PS).…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…On the other hand, following longer exposure to directional motion the sensor signals a direction opposite to the adapting pattern (i.e., rMAE). Thus, the final output of the second-order model shows effects which mirror those reported by previous psychophysical studies on fast forms of motion adaptation (Kanai and Verstraten 2005;Pavan et al 2009Pavan et al , 2010Glasser et al 2011;Pavan and Skujevskis 2013). The extended Motion Energy Model does not account for another effect previously reported by Kanai and Verstraten (2005) and Pavan et al (2009Pavan et al ( , 2010, called "Perceptual Sensitization" (PS).…”
Section: Discussionsupporting
confidence: 63%
“…When two stimuli are presented in rapid succession, the neural response to the latter stimulus is considerably reduced, a phenomenon well known as short-term synaptic depression (Nelson 1991;Finlayson and Cynader 1995;Varela et al 1997Varela et al , 1999Chance et al 1998;Lisberger and Movshon 1999;Boudreau and Ferster 2005). Short-term synaptic depression has been reported within the striate cortex of cats (Boudreau and Ferster 2005) and also in area MT of monkeys (Lisberger and Movshon 1999;Glasser et al 2011). , for example, found that monkey MT neurons respond to a motion step with a transient-sustained firing rate.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Neurophysiological studies have shown that a moving stimulus with a very short duration, such as several hundred milliseconds, is sufficient to change the adaptation status of directionally selective neurons located at V1 [46]. This type of rapid adaptation of directionally selective neurons is assumed to be an underlying mechanism of motion contrast (or rMAE) [47]. In contrast with our study, van Loon et al [3] found that the GABA concentration in the V1, but not the Glx concentration in the PFC, is correlated with the dynamics of visual bistable perception.…”
Section: Discussionmentioning
confidence: 99%